Classroom Interactions Inspeaking Class Of English Department Of Muhammadiyah University Of Surakarta - Kusuma Suci, Dian; , Prof. Dr. Endang Fauziati, M. Hum; , Mauly Halwat Hikmat, Ph. D (2015)
The paper describes the types of classroom interactions occur in speaking class of English Department of Muhammadiyah University of Surakarta. Subject of the research consisted of third semester students of English Department of Muhammadiyah University of Surakarta. The data gathering was conducted by observation and open - ended interview with the participants. The data were analyzed qualitatively. The result of the research indicated the dominant type of classroom interaction is teacher - student interaction. This implies that the students have been most interacted with the teacher in the class which resulted in the learning outcomes.As the interaction are essential in classroom, it is expected that the teacher can create more interesting activities leads to active interactions in the class between teacher and students as well as among students.